Exploratory analysis using MRM profiling mass spectrometry of a candidate metabolomics sample for testing system suitability - Edwards, Madison E.; Marasco, César A. [UNESP]; Schock, Tracey B.; Sobreira, Tiago J.P.; Ferreira, Christina R.; Cooks, R. Graham (Elsevier, 2021)
Multiple reaction monitoring (MRM) profiling is an exploratory mass spectrometry (MS) method applicable to the initial screening of complex samples for small molecules based on their chemical functionalities. We report on the applicability and quality of this method to screen for metabolites, lipids and exogenous compounds in a candidate reference material, the Metabolomics System Suitability Research Grade Material (RGM 10122) which is being developed by the National Institute of Standards and Technology (NIST). In an initial discovery experiment, we recorded data using eighty neutral loss (NL) and precursor ion (Prec) MS/MS scans, selected from literature data as likely of value in recognizing the presence of potential lipids and metabolites. Then the NIST sample was re-examined combining precursor-to-product ion transitions from the discovery experiment with a list of 1357 known literature-based metabolite MRMs. This MRM profiling experiment gave a small set (191) of high-quality lipid specific MRMs for the sample. Similar experiments gave 104 and 17 metabolite and exosome MRM's. These MRM experiments, with a few exceptions, showed relative standard deviations (RSD) under 25% for individual tentatively assigned compounds. At a data acquisition rate of 50 compounds/min, using two MRMs for each compound, this approach allows quick surveys for easily detectable compounds in complex samples.
Keywords: Exposome; Lipidomics; Metabolomics; NIST RGM 10122; Reproducibility; Tandem mass spectrometry